The toll of COVID-19 on restaurant business and the future in Zimbabwe: Case of Manicaland province - Vitalis Basera; Absai Chakaipa; Krammer Chatiza; Nevermind Muchongwe; David Chibhoyi; Bernard Chisiri (Bahasa Indonesia, 2022)
COVID-19 has wreaked havoc throughout the world across economies and social strati as evident from literature. Numerous employees lost their jobs across industries and the hardest hit industry is the tourism and hospitality industry. Restaurant business is a bigger component of tourism industry and many restaurants’ workers were left job less due to COVID-19. This study sought to investigate the toll of COVID-19 on restaurants business. The country is strategising towards attaining an upper middle income economy status by year 2030 (Vision 2030) using National Development Strategy 1 (NDS) and the study noted the concerns of restaurant workers and restaurateur towards Vision 2030. Recommendations to keep in line with the dictates of NDS are given from the study. The study followed a case study approach were restaurants in Manicaland province were used as a representative sample for the whole industry in Zimbabwe. Only Zimbabwe Tourism Authority (ZTA) registered players were considered in this study. Data was collected using questionnaires and SPSS version 21 in conjunction with the R software were used for data analysis. The researchers gathered data from restaurateurs, restaurant workers and key industry stakeholders including ZTA, Hospitality Association of Zimbabwe (HAZ) and Restaurant Association of Zimbabwe (ROAZ). The research results reflected that COVID-19 had impacted negatively on restaurant business in Zimbabwe; worker retrenchments and restaurateurs’ bankruptcy. For sustainable restaurant business in the future, the paper recommended the restaurateurs to join the restaurant operators association for engagement with government.